Genomic and functional analysis of Romboutsia ilealis CRIBT reveals adaptation to the small intestine - Jacoline Gerritsen; Bastian Hornung; Bernadette Renckens; Sacha A.F.T. van Hijum; Vitor A.P. Martins dos Santos; Ger T. Rijkers; Peter J. Schaap; Willem M. de Vos; Hauke Smidt (PeerJ, 2017)
Background The microbiota in the small intestine relies on their capacity to rapidly import and ferment available carbohydrates to survive in a complex and highly competitive ecosystem. Understanding how these communities function requires elucidating the role of its key players, the interactions among them and with their environment/host. Methods The genome of the gut bacterium Romboutsia ilealis CRIBT was sequenced with multiple technologies (Illumina paired-end, mate-pair and PacBio). The transcriptome was sequenced (Illumina HiSeq) after growth on three different carbohydrate sources, and short chain fatty acids were measured via HPLC. Results We present the complete genome of Romboutsia ilealis CRIBT, a natural inhabitant and key player of the small intestine of rats. R. ilealis CRIBT possesses a circular chromosome of 2,581,778 bp and a plasmid of 6,145 bp, carrying 2,351 and eight predicted protein coding sequences, respectively. Analysis of the genome revealed limited capacity to synthesize amino acids and vitamins, whereas multiple and partially redundant pathways for the utilization of different relatively simple carbohydrates are present. Transcriptome analysis allowed identification of the key components in the degradation of glucose, L-fucose and fructo-oligosaccharides. Discussion This revealed that R. ilealis CRIBT is adapted to a nutrient-rich environment where carbohydrates, amino acids and vitamins are abundantly available.